2006
DOI: 10.1080/14992020600783079
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported benefits from successive bilateral cochlear implantation in post-lingually deafened adults: randomised controlled trial

Abstract: Adult users of unilateral Nucleus CI24 cochlear implants with the SPEAK processing strategy were randomised either to receive a second identical implant in the contralateral ear immediately, or to wait 12 months while they acted as controls for late-emerging benefits of the first implant. Twenty four subjects, twelve from each group, completed the study. Receipt of a second implant led to improvements in self-reported abilities in spatial hearing, quality of hearing, and hearing for speech, but to generally no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 20 publications
5
114
1
1
Order By: Relevance
“…For sequential implantation, improvement in QOL was seen in assessment on a social-emotional-psychological subscale but a statistically significant decrease in a generic QOL outcome assessor that was mainly attributable to tinnitus in 2 participants. 43 We did not perform a quantitative synthesis of these results because of heterogeneity in design between the studies.…”
Section: Qol Outcomes In Bilateral Implantationmentioning
confidence: 99%
See 2 more Smart Citations
“…For sequential implantation, improvement in QOL was seen in assessment on a social-emotional-psychological subscale but a statistically significant decrease in a generic QOL outcome assessor that was mainly attributable to tinnitus in 2 participants. 43 We did not perform a quantitative synthesis of these results because of heterogeneity in design between the studies.…”
Section: Qol Outcomes In Bilateral Implantationmentioning
confidence: 99%
“…Three studies 31,43,55 assessed QOL in recipients of bilateral vs unilateral cochlear implants (across groups or within subjects). Two of these studies 31,55 showed a significant benefit across 5 subscales of 3 different hearingrelated QOL tests but no change in the subscales that assessed emotional QOL and aversion to sound in patients with simultaneous bilateral implantation.…”
Section: Qol Outcomes In Bilateral Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…improving speech understanding for persons with severe-to-profound hearing loss. The benefits of cochlear implantation have been well documented and include better speech perception in quiet and noise (e.g., Parkinson et al, 2002;Tyler et al, 1995Tyler et al, , 2002Waltzman et al, 1999) and an improved quality of life (e.g., Maillet et al, 1995;Summerfield et al, 2006;Vermeire et al, 2005). Research also suggests that bilateral device use through two cochlear implants (CI+CI) or a cochlear implant plus hearing aid in opposite ears (CI+HA) provides important auditory cues to both ears, thus allowing for potential binaural hearing advantages (Armstrong et al, 1997;Ching et al, 2001Ching et al, , 2004Ching et al, , 2005Dorman et al, 2004;Dunn et al, 2005;Litovsky et al, 2006;Luntz et al, 2005;Laszig et al, 2004;Morera et al, 2005;Shallop et al, 1992;Tyler et al, 2002Tyler et al, , 2006Tyler et al, , 2007van Hoesel & Tyler, 2003;Waltzman et al 1992).…”
mentioning
confidence: 99%
“…In the case of electrical stimulation, Dobie (2004a) noted that if an implantable electrical device could be realized, it may offer relief for some patients (there are cases of tinnitus suppression among cochlear implant users; Rubinstein & Tyler, 2004; there are also cases of tinnitus exacerbated by implantation; Summerfield et al, 2006). De Ridder et al (2006 reported promising results of implantation in the auditory cortex of 12 patients.…”
Section: Acoustic-physical Treatments: Review Of Evidencementioning
confidence: 99%